Manajemen Pemberian Antibiotik dengan Hasil Uji Kepekaan Resisten: [Management of Antibiotics Use with Resistant Sensitivity Test Results] - Deny Perdana Putra; Tutik Kusmiati (Jurnal Respirasi, 2015)
The use of antibiotics in developed countries 13-37% and 30-80% in developing countries. Inappropriate use of antibiotics around 40-62%. There is a relationship between the use of antibiotics in bacterial resistance. Reported a man, 45 years old with a diagnosis of pneumonia + sepsis + DM Type 2 + hypoalbuminemia + anemia + suspek nephrotic syndrome. Empirical therapy is given Meropenem and Levofloxacin 1 750 3 1 grams milligrams. Evaluation after empirical therapy showed no improvement clinically and radiologically. The result of the patient ‘s sputum cultures of Pseudomonas aeruginosa which are resistant to antibiotics tested, therefore the definitive therapy can not be given based on antibiotic susceptibility. The cause of this multifactorial resistance in patients with Pseudomonas resistance to antibiotics through four mechanisms. Therefore, definitive therapy based on local patterns of bacteria and sensitivity test on pneumonia issued by the Department of Microbiology Clinic. Based on the data, antibiotic Piperacillin-tazobactam 4 4, 5 grams are then administered. The results of the evaluation of clinical, radiological and laboratory showed significant improvements in patients.